PENGARUH PERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XI SMA NEGERI 1 PARIAMAN - Pebriyanti, Rani (Departemen Matematika, 2024)
The whole point of teaching math is to help students become better communicators in the subject. Class XI SMAN 1 Pariaman students still lack even the most basic of these abilities, though. Among these endeavours was the implementation of the Think-Talk-Write (TTW) cooperative learning approach. A pseudo-experiment with a randomised control group design was utilised for this study. Mathematical communication skills learned using the TTW model outperform those learned using standard models in eleventh grade SMAN 1 Pariaman, according to data analysis. There has been an uptick in skill development as a result of using the TTW paradigm.Keywords– Think Talk Write, Mathematical Communication Skills, Traditional Teaching